Fekete-Szegö Inequality for a Subclass of Bi-Univalent Functions Associated with Hohlov Operator and Quasi-Subordination (Communications in Mathematical Research, 2019)
In this paper, we introduce a new subclass of bi-univalent functions defined by quasi-subordination and Hohlov operator and obtain the coefficient estimates and Fekete-Szegö inequality for function in this new subclass. The results presented in this paper improve or generalize the recent works of other authors.
Keywords: analytic function; univalent function; bi-univalent function; coefficient estimate; Fekete-Szegö inequality; Hohlov operator; quasi-subordination